2021
DOI: 10.1055/a-1327-2025
|View full text |Cite
|
Sign up to set email alerts
|

Transpancreatic biliary sphincterotomy versus double guidewire in difficult biliary cannulation: a randomized controlled trial

Abstract: Background Difficult biliary cannulation in endoscopic retrograde cholangiopancreatography (ERCP) increases the risk of post-ERCP pancreatitis (PEP). The purpose of this prospective, randomized, multicenter study was to compare two advanced rescue methods, transpancreatic biliary sphincterotomy (TPBS) and a double-guidewire (DGW) technique, in difficult common bile duct (CBD) cannulation. Methods Patients with native papilla and planned CBD cannulation were recruited at eight Scandinavian hospitals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The method was spearheaded by the Helsinki group, who showed that the method compared favorably to free-hand precut in a large retrospective multicenter trial [15] . More recently, a systematic review also concluded that the method offered a higher cannulation success rate compared to the relevant alternatives, with a similar complication rate [16] . A recent randomized comparison found a comparable PEP risk, but a higher cannulation success rate (85% vs. 70%) in transpancreatic sphincterotomy vs. double-wire technique [17] .…”
Section: Transpancreatic Sphincterotomymentioning
confidence: 97%
“…The method was spearheaded by the Helsinki group, who showed that the method compared favorably to free-hand precut in a large retrospective multicenter trial [15] . More recently, a systematic review also concluded that the method offered a higher cannulation success rate compared to the relevant alternatives, with a similar complication rate [16] . A recent randomized comparison found a comparable PEP risk, but a higher cannulation success rate (85% vs. 70%) in transpancreatic sphincterotomy vs. double-wire technique [17] .…”
Section: Transpancreatic Sphincterotomymentioning
confidence: 97%
“…6. Evidence-based ESGE algorithm for biliary cannulation in ERCP [1], modified according to local standards and update of evidence [46,68]. The exact technique/sequence of techniques for overcoming a DBC situation should always be selected after careful consideration with regard to patient anatomy, underlying pathology, and endoscopist's preference and level of expertise.…”
Section: Anterograde Access Techniquesmentioning
confidence: 99%
“…We thank Drs. Sundaram and Jagtap for their comments concerning our article "Transpancreatic biliary sphincterotomy versus double guidewire in difficult biliary cannulation: a randomized controlled trial," which was recently published in Endoscopy [1]. In our multicenter study, transpancreatic biliary sphincterotomy (TPBS) was performed when the guidewire was inside the pancreatic duct (PD) and access to the common bile duct (CBD) was gained by cutting the septum between the PD and CBD with the sphincterotome toward the 11 o'clock position.…”
Section: Reply To Sundaram and Jagtapmentioning
confidence: 99%